Perempuan Bicara dalam Majalah Dunia Wanita: Kesetaraan Gender dalam Rumah Tangga di Indonesia, 1950-an - Siti Utami Dewi Ningrum (Universitas Gadjah Mada, 2018)
Women’s voices have emerged since the colonial era through writing. Kartini became the most heard through her radical letters at the time, published with the title Door Duisternis tot Licht, voicing the fulfillment of women’s education. Women’s writings were increasingly seen in women’s magazines from colonial times to independence of Indonesia, which published by women’s organizations although commercial magazines. Each of them has a very unique and diverse idea.Dunia Wanita has become one of the popular women’s magazines after Indonesian independence. Presenting various women’s issues from the social, political and economic fields to provide information and progress for women. Under the leadership of Ani Idrus, this magazine also voiced the importance of the involvement of men in the household, a theme that was faintly heard among the frenzied Indonesian political conditions at the beginning of its independence.What is equality in the household voiced by women in Indonesia through the 1950s in Dunia Wanita? This will be discussed in historical writings with gender perspective analysis. In addition to using articles in Dunia Wanita, this paper also uses other magazines as a comparison. In addition, books and papers that are relevant to the theme of the writing are also used.